Rákos betegek mentális és lelki kísérése - BALOGH, Gyöngyi (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Mental and Spiritual Accompaniment of Cancer Patients This paper explores the mental and spiritual accompaniment of cancer patients from a theological and pastoral perspective. The author reflects on her early experiences as a hospital chaplain and the challenges of communicating hope and comfort to patients facing a life-threatening diagnosis. She reviews the current literature on the psychological, social, and spiritual aspects of cancer and how they affect patients’ coping strategies, quality of life, and meaning making. She also discusses the role of the Church and its functionaries in providing support and guidance to cancer patients, as well as the potential benefits of what a theologically reflected service can offer in extension to other approaches. The paper emphasizes the importance of understanding the patients’ emotional, relational, and spiritual needs and of respecting their individuality and dignity. The paper also highlights the supreme relevance of the Christian faith as a source of hope for cancer patients. The paper concludes with some practical suggestions for pastoral care and spiritual accompaniment of cancer patients.